(untitled) (Journal of Environmental Science and Natural Resources, 2021)
An experiment was conducted to produce ethanol/biofuel from cassava flour which reduce both consumption of crude oil and environmental pollution. Cassava flour hydrolysate with standard glucose and sucrose solutions were used as controls. The effects of yeast concentrations (5, 15 and 20%) and fermentation time (24, 48, 72, 96 and 120 h) on alcohol yield from CFH were also studied. The maximum carbon-dioxide evolved during fermentation was 8.57 g recorded by cassava flour hydrolysate while the conversion efficiency of sugars to alcohol was 247.6, 97.14 and 92.51% for cassava flour hydrolysate, standard glucose and sucrose solutions, respectively. Alcohol produced was mostly ethanol with traces of methanol. However, yeast concentrations did not showed any significant effect but fermentation time had significant impact on alcohol yield which suggests that the high yield of alcohol could be obtained from cassava flour hydrolysate. Environ. Sci. & Natural Resources, 12(1&2): 171-174, 2019